Twin pregnancy resulting from ovodonation in a case of Turner syndrome - Quispe, José (2015)
OBJETIVO: A case of Turner's syndrome mosaicism who became pregnant with oocyte donation and embryo transfer is presented. SETTING: Ricardo Palma Clinic Assisted Reproduction Center: MATERIAL AD METHODS: 32 year-old patient with Turner's syndrome 45,X/47,XXX/46,XX and primary infertility. The endometrium was prepared for implantation with increasing doses of estradiol valerate 2 to 8 mg/daily, until endometrial thickness was obtained and retrieval day was calculated. Luteal support was with transvaginal micronized progesterone 1200 mg/daily. Controlled ovarian hyperstimulation was done with GnRH analogs and FSHr. Nine eggs were retrieved, 5 used and 3 embryos transferred in the next 48 hours. Currently the patient carried a II trimester twin pregnancy. CONCLUSIONs: In vitro fertilization with oocyte donation is an alternative for infertility in Turner's syndrome. The intrauterine embryo transfer can be performed in patients with normal uterine cavity.